Research and prospect of intelligent connected vehicle test scheme - Dongsheng WU; Fengna LI; Ningxin XIA; Dacheng LI (Dianxin kexue)
The comprehensive test and evaluation of intelligent connected vehicles is an important guarantee for the safety of intelligent connected vehicles on the road and the smooth landing of the industry.Based on the test status, test technology path, test evaluation specifications and standards of intelligent connected vehicles, the overall architecture of intelligent connected vehicle test scheme was proposed innovatively in terms of meeting the existing road test requirements of intelligent connected vehicles and future multi-application integration.And the virtual simulation test, network connection test, automatic driving function test, large-scale concurrent test and interconnection test five business applications were elaborated.Finally, combining the practical application and industry demands of intelligent connected vehicles, the future development directions of intelligent connected vehicle test were prospected.